RANCANGAN SISTEM PENGUKURAN KINERJA KARYAWAN MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS - Widayati, Qoriani (Universitas Bina Darma, 2013)
The quality of human resources is one of factor thatâs needed to increase the performance productivity in an institution. PT Kereta Api Indonesia (Persero) as a service company assessment of performance variables at the top. Are subjective measurements that are meaningful measurements based on personal opinion or personal standards of people who do the assessments and it is difficult to verify by others. Required a computerized design system for the assessment of employees at PT Indonesia Railways (Limited). To calculate the required method of assessment indicators that can be used for the measurement of employee performance PT Indonesia Railways (Limited). One method used in this study is the method of Analytical Hierarchy Process (AHP). The concept of AHP method is to change the qualitative values into quantitative values, so that bias decisions more objective. Keywords: Employee Performance, AHP, and Prototyping